God's blueprint for marriage--participant guide - Collier, John, 1969-; Collier, Julie, 1969- (Birmingham : Life Bible Study, 2024)
"Drawing from their years of marriage and ministry, John and Julie Collier have created a small-group marriage workbook to help couples put God in the center of their marriage. Based in scripture, this twelve-week study will guide couples on praying together, spending quality time together, and finding joy in each other"--